Implementasi Yudas 1:17-25 Bagi Pertumbuhan Remaja Kristen - Ayu Niken Waoma; Abad Jaya Zega (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The main concepts in this chapter, namely, keeping oneself in God's love, praying in the Holy Spirit, and waiting for God's grace, are analyzed to understand their impact on Christian teenagers' character, identity, and faith development. The results show that the implementation of these concepts positively affects the way Christian teenagers view themselves, their relationship with God, and their attitude toward the future. A strong hope in God's grace becomes an important pillar in their spiritual growth. Research on the implementation of Jude 1:17-25 for the growth of Christian teenagers can be carried out using qualitative research methods. This method allows the researcher to go deep into the understanding and experience of Christian teenagers related to the verse. The concept of "keeping oneself in the love of God" changes the way they understand their identity, while "praying in the Holy Spirit" helps them get closer to God personally. Furthermore, "waiting for God's mercy" creates an attitude of hope that brings them through difficult times with courage. The findings provide valuable insights into how we can support the spiritual growth of Christian teenagers through the implementation of the concepts of Jude 1:17-25.